Facebook Use as Mechanism in Understanding Emotion and Self-regulation - Aclao, Joel; Cabrera, Joey A.; Abucay, Ell June S.; Colegado, Cleo Wendell Jade Z. (JPAIR Multidisciplinary Research, 2013)
Schools and school administrators regulate the use of social networking sites especially Facebook in the campus as they consider it unfavorable to students' academic life. This study looked into the positive contribution of Facebook to students' life. It correlated students' frequency of Facebook use and their level of emotion regulation. This descriptive-correlational study utilized Emotion Regulation Questionnaire to collect data from the 130 student-respondents. The study revealed that the Misamis University High School students used Facebook for 1-2 hours a day on average. As the students increase their frequency of Facebook use, their level of understanding and regulating their emotion get better. The study reconsiders revision of the school policy on Facebook use in the campus and integration of the same in instructional practices.
Keywords: Educational Psychology; Facebook Use; Understanding Emotion; Self-regulation; Descriptive-Correlational Study; Philippines